Influenza Infection Screening Tools Fail to Accurately Predict Influenza Status for Hospitalized Patients During Pandemic H1N1 Influenza Season - Sunita Mulpuru; Virginia R Roth; Nadine Lawrence; Alan J Forster (Canadian Respiratory Journal)
BACKGROUND: Following the severe acute respiratory syndrome outbreak in 2003, hospitals have been mandated to use infection screening questionnaires to determine which patients have infectious respiratory illness and, therefore, require isolation precautions. Despite widespread use of symptom-based screening tools in Ontario, there are no data supporting the accuracy of these screening tools in hospitalized patients.